Father and Daughter: A Recovered Link in Chitra Banerjee Divakaruni’s Queen of Dreams - Gouaux‑Rabasa, Laurence (Romanica Silesiana)
Chitra Banerjee Divakaruni is an English-speaking writer who was born in India in 1956 and is currently living in the United States. In Queen of Dreams published in 2004 she depicts the conflicts between Rakhi, a young American in her thirties living in California, and her India-born parents. Rakhi reproaches them for refusing to initiate her to Indian culture, particularly blaming her father for not being able to communicate. However, the mother’s death is the trigger for the father’s story. The father becomes the one who tells his daughter about life in India, thus embodying the missing cultural link in Rakhi’s family tree. The aim of this article is to offer an analysis of the father-daughter relationship as presented in Queen of Dreams. It intends to put into light the part played by the father in helping his daughter understand the way transgenerational loyalties work, and create a new identity of her own.